Pilot scale production of the vaccine adjuvant Proteoliposome derived Cochleates (AFCo1) from Neisseria meningitidis serogroup B - Zayas, Caridad; González, Domingo; Acevedo, Reinaldo; del Campo, Judith; Lastre, Miriam; González, Elizabeth; Romeu, Belkis; Cuello, Maribel; Balboa, Julio; Cabrera, Osmir; Guilherme, Luisa; Pérez, Oliver (BMC immunology, 2013)
The use of new adjuvants in vaccine formulations is a subject of current research. Only few parenteral adjuvants have been licensed. We have developed a mucosal and parenteral adjuvant known as AFCo1 (Adjuvant Finlay Cochleate 1, derived from proteoliposomes of N. meningitidis B) using a dialysis procedure to produce them on lab scale. The immunogenicity of the AFCo1 produced by dialysis has been already evaluated, but it was necessary to demonstrate the feasibility of a larger-scale manufacturing process. Therefore, we used a crossflow diafiltration system (CFS) that allows easy scale up to obtain large batches in an aseptic environment. The aim of this work was to produce AFCo1 on pilot scale, while conserving the adjuvant properties. The proteoliposomes (raw material) were resuspended in a buffer containing sodium deoxycholate and were transformed into AFCo1 under the action of a calcium forming buffer. The detergent was removed from the protein solution by diafiltration to a constant volume. In this CFS, we used a hollow fiber cartridge from Amicon (polysulfona cartridge of 10 kDa porosity, 1mm channel diameter of fiber and 0.45 m 2 area of filtration), allowing production of a batch of up to 20 L. AFCo1 were successfully produced by tangential filtration to pilot scale. The batch passed preliminary stability tests. Nasal immunization of BALB/c mice, induced specific saliva IgA and serum IgG. The induction of Th1 responses were demonstrated by the induction of IgG2a, IFNγ and not IL-5. The adjuvant action over Neisseria (self) antigens and with co-administered (heterologous) antigens such as ovalbumin and a synthetic peptide from haemolytic Streptococcus B was also demonstrated.